A Tale of Two Foreign Languages: A Comparison of the Methods Used by Arabic and English Teachers’ Used in High School Classes - Arezoo Qolinejad Kamarposhti (Journal of Education and Teacher Training Innovation, 2025)
Both Arabic and English as foreign languages are compulsory in Iranian high schools and have been taught for decades. The textbooks and teaching methods which have been used in Arabic and English classes in high schools have undergone so many changes in the past decades in Iran. Unlike teaching Arabic as a foreign language, in Iran, teaching English as a foreign language has been in the cannon of attention in terms of the volume of research done on both the language and teaching methodologies. This implies that teaching these two languages has been dealt with different out of the class. This research aims at tracing such a difference within a single class through a case study method. Qualitative case study research using classroom observation and retrospective interview was utilized to see two teachers, one teaching Arabic and the other teaching English adopt different teaching methods within a single class. The analysis of field notes from eight hours of observation and the data from the semi-structured interviews showed that the teachers adopted quite different methods in the class. While the English teacher was linguistically oriented focusing on morphosyntactic rules, the Arabic teacher focused on translation and every-day use of language relying on community related examples, some of which were created by the students themselves. Moreover, the English teacher bolded the use of technological aids for teaching, especially, use of multimedia. The pedagogical implications of the findings were discussed, according to the findings of the study